Corporate Marketing Planning (Global Journal of Management and Business Research, 2014)
Corporate marketing planning is the process by which an organization sets its long-term priorities regarding products and markets in order to enhance the value of the overall company. It is in corporate strategy, management identifies the business in which the company will be involved in the future by specifying the range of markets to be served and the kinds of products to be offered. In marketing corporate strategy decisions the critical question to be answered is in what markets will our particular resources be most effective in implementing the marketing concept. Once incorporate strategy has been chosen, management must develop a product mix strategy to identify the role each product is expected to play in building the value of business. The relative share of the firms resources to be devoted to each product of product line. This paper is focus on cooperate marketing planning.